Safety of maternal pertussis vaccination on pregnancy and birth outcomes: A prospective cohort study. Issue 2 (8th January 2021) - Mohammed, Hassen; Roberts, Claire T; Grzeskowiak, Luke E; Giles, Lynne C; Verburg, Petra E; Dekker, Gustaaf; Marshall, Helen S
Abstract: Objective: To evaluate the safety of maternal pertussis vaccination on pregnancy and birth outcomes. Methods: The study population comprised 1272 healthy nulliparous pregnant women who participated in Screening Tests to identify poor Outcomes in Pregnancy (STOP) study at two obstetric hospitals in South Australia between 2015 and 2018. Participants were followed prospectively, with vaccination (confirmed by medical records), extensive amounts of pregnancy and birth outcome data collected by research midwives. Adjusted relative risks (aRRs) and hazard ratios (aHRs) were estimated accounting for time-varying vaccine exposure and the temporal nature of each outcome. Results: Of the 1272 women included in this study, 80.1% (n = 1019) received maternal pertussis vaccination. Vaccinated women had an average 0.22 weeks (95% CI 0.001, 0.44) longer gestation at delivery compared to unvaccinated women. Maternal pertussis vaccination was not associated with chorioamnionitis (aRR 0.71, 95% CI 0.27, 1.82), gestational hypertension (aHR 1.24, 95% CI, 0.66, 2.30), preeclampsia (aHR 0.75, 95% CI 0.47, 1.18) nor preterm birth (aHR 0.99, 95% CI 0.47, 2.07). Neither risk of low birth weight (aHR 0.72, 95% CI 0.41, 1.27) nor small for gestational age infants (aHR 0.67, 95% CI 0.29, 1.55) were increased following maternal pertussis vaccination. No associations between pertussis vaccination during pregnancy and adverse birth outcomes including admission to the neonatal care unit, low Apgar scores, and mechanical ventilation were observed. Results were not materially changed after adjustment for maternal influenza vaccination. Conclusion: Our study provides reassuring evidence of the safety of maternal pertussis vaccination with no increased risk of adverse pregnancy and birth outcomes. These findings support recommendations for pertussis vaccination during pregnancy to prevent morbidity and mortality associated with early-infant pertussis disease.